Household Conflict And Its Impact On The Quality Of Life Of Wife And Children in Bogor - Jannah, Aisyah Al Jannatun Kharomah; Ikhwan , Ikhwan Hamdani; Ade Irma , Ade Irma Imamah; Istikhori (MIZAN: JOURNAL OF ISLAMIC LAW, 2025)
This study aims to examine the efforts of wives in dealing with domestic conflicts, the impact of these conflicts, and the factors that affect wives to maintain household integrity amid conflicts in Pasirangin, Cileungsi District. Domestic conflicts in this village are triggered by the husband’s negligence in providing maintenance, domestic violence, injustice in the practice of polygamy, and the husband’s demand for his wife to earn a living. The impact of conflict includes economic, psychological, and educational aspects. This study uses a descriptive qualitative approach through field research methods. Data were collected through observation, interviews, and documentation with research subjects of a group of wives in Pasirangin Village. The results of the study showed three main findings, namely, the way wives deal with domestic conflicts, the impact of conflicts on the quality of life of wives and children, and factors that encourage wives not to file for divorce to maintain the integrity of the household. This research provides insight into the dynamics of household conflict and family resilience in rural social contexts. Keywords: domestic conflict; responsibility; quality of life of wife and children